PASSIONATE LOVE IN PABLO NERUDA’S POEMS DRUNK AS DRUNK, YOUR FEET, AND YOUR HANDS - Pujimahanani, Cahyaningsih; Elindriani, Yulia Prastika (Dinamika : Jurnal Sastra dan Budaya, 2017)
This study aims to analyze Passionate Love in Pablo Neruda?s Poems Drunk as Drunk, Your Feet, and Your Hands. The objectives of the study are: (1) to find out the elements of passionate love in Pablo Neruda?s poems Drunk as Drunk, Your Feet, and Your Hands; and (2) to find out the factors contributing passionate love in Pablo Neruda?s poems Drunk as Drunk, Your Feet, and Your Hands. The theory used by the thesis writer is the theory of Passionate Love by Psychologist Elaine Hatfield and she also applies a qualitative research. Key words: Love, Passionate Love, Intense Feelings, Sexual Attraction.